A Status Evaluation of Rock Instability in Metal Mines Based on the SPA–IAHP–PCN Model - Fang Yan; Xuan Li; Longjun Dong; Shengnan Du; Hongwei Wang; Daoyuan Sun (Applied Sciences)
As one of the serious hazards in deep mining, rock instability will cause roof falls, rib spalling, rockburst, and other serious disasters. It will lead to significant casualties and property losses. Conducting risk assessments for rock instability is of significant importance. Firstly, an evaluation model called IAHP-SPA was proposed to address uncertainties in the weight determination process. Secondly, the Partial Connection Number (PCN) including the first-order PCN, the second-order PCN, the third-order PCN and the fourth-order PCN were introduced. Thus, a dynamic and comprehensive evaluation of rock instability in metal mines was obtained. Finally, the availability and reasonability of the proposed method were verified by comparing the results obtained with the number of microseismic events detected by the sensors in a metal mine. The proposed model provides a novel approach to dynamic risk assessment in mining, offering a reliable alternative for evaluating complex safety challenges. This method holds substantial potential for its practical application in the assessment and control of rock instability risks in deep metal mines, thereby improving safety and operational efficiency.